Pemasaran Digital dan Customer Relationship Management: Upaya Meningkatkan Kemampuan UMKM dalam Membangun Relasi Pelanggan - Riptiono, Sulis (JCSE: Journal of Community Service and Empowerment, 2025)
This Community Service activity aims to improve the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) in utilizing digital marketing and implementing Customer Relationship Management (CRM) as a strategy to strengthen customer relationships and improve business performance. The training was conducted through a lecture method for 30 participants, covering an introduction to digital marketing, strategies for utilizing social media, and implementing customer data-based CRM. The results of the activity showed a significant increase in participants' abilities in using social media platforms for promotions, conducting digital interactions with consumers, and managing and analyzing customer data in a more structured manner. Overall, this activity has made a positive contribution to MSMEs in facing competition in the digital era. This training is expected to be the first step for MSMEs to continue developing technology-based marketing strategies and implementing CRM sustainably in their business operations.